2018
DOI: 10.1177/1010428318772202
|View full text |Cite
|
Sign up to set email alerts
|

Technical and clinical performance of a new assay to detect squamous cell carcinoma antigen levels for the differential diagnosis of cervical, lung, and head and neck cancer

Abstract: In squamous cell carcinoma, squamous cell carcinoma antigen levels are often elevated. This multi-center study evaluated the technical performance of a new Elecsys Ò squamous cell carcinoma assay, which measures serum squamous cell carcinoma antigen 1 and 2 levels in an equimolar manner, and investigated the potential of squamous cell carcinoma antigen for differential diagnosis of cervical, lung, and head and neck squamous cell carcinoma.Assay precision and method comparison experiments were performed across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
(80 reference statements)
0
13
0
Order By: Relevance
“…[15][16][17] At present, few studies of serum SCCA have been reported in various types of pan squamous cell cancer and the difference between different detect system remains to be clarified. Although Holdenrieder et al study 13 evaluated the clinical value of biomarker As a first step, we evaluated the method's precision using the controls provided by the manufacturer. The precision studies showed the accuracy of both instruments with the control values within the specified range (<10%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] At present, few studies of serum SCCA have been reported in various types of pan squamous cell cancer and the difference between different detect system remains to be clarified. Although Holdenrieder et al study 13 evaluated the clinical value of biomarker As a first step, we evaluated the method's precision using the controls provided by the manufacturer. The precision studies showed the accuracy of both instruments with the control values within the specified range (<10%).…”
Section: Discussionmentioning
confidence: 99%
“… 15 - 17 At present, few studies of serum SCCA have been reported in various types of pan squamous cell cancer and the difference between different detect system remains to be clarified. Although Holdenrieder et al study 13 evaluated the clinical value of biomarker for the differential diagnosis of squamous cell carcinoma of cervical, lung, head and neck, this study did not analyze other squamous cell carcinomas. In the present study, Abbott I2000 and Roche e 602 detection systems were the first time compared among various squamous cell carcinomas, including squamous cell carcinoma of NPC, head and neck, esophageal, lung, bladder and cervical.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative active amino acid composition of Trx is Cys-Gly-Pys-Cys, and Trx can catalyze the redox reaction and also maintain intracellular homeostasis, regulate apoptosis and resist oxidative stress response under biological functions (11). A number of studies have demonstrated that the expression of Trx is increased in a variety of malignant tumors, such as gastric, breast, liver, lung, rectal and cervical cancers (7,12), indicating that Trx is closely related to malignant tumors. It was found in related studies that Trx can inhibit apoptosis of tumor cells, promote cell proliferation and disturb normal cell cycle (13).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CYFRA21-1 is considered as one of the best tumor markers for detecting lung cancer (6). Serum squamous cell carcinoma antigen (SCCA) is a tumor-associated antigen, and its levels in serum and specificity are higher in lung cancer patients (7). No lung cancer marker with good specificity and sensitivity has been found yet.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the most widely used SCC-Ag assay in clinical settings is proposed by Abbott on the Architect instrument (Abbott Laboratories, Abbott Park, IL, USA) [7,8]. SCC-Ag assays are also available on other wellknown platforms, such as the Elecsys® SCC assay used on the Roche Elecsys and cobase analyzer (Roche Diagnostics, China) [9].…”
Section: Introductionmentioning
confidence: 99%